The Effects of food Quality of Cyprinus Carpro L Growth During winter in the middle region of Iraq (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
See PDF please. During the period between211211993 .md ~i311994, CyprinuscapIQ L. were feed on differnt levels ofcommercial foof with the use of(27 : chemical fertilization "\\ith N:P27) The experiments showed nosignificant differences between thegrowth of fishes in all treatmentsreCl\'IDg feed. However. feeding atlevel (1 '}(» of fises weight fllll give thebest results hecause of the low rGodconversion ratio and COS1.